Development And Implementation Of Occupational Safety And Health With Job Safety Analysis In Civil Engineering Laboratories - Barry Yusuf Labdul; Hamsu Abdul Gani; Purnamawati, Purnamawati (International Journal of Education, Vocational and Social Science, 2024)
Occupational safety and health (OSH) practices and Job Safety Analysis (JSA) are crucial for ensuring the well-being of workers and students in civil engineering laboratories. This study investigates the development and implementation of OSH practices with JSA in civil engineering laboratories to enhance safety performance and reduce accident risks. The research draws insights from various industrial settings, including construction and manufacturing, where JSA has been widely applied to identify and mitigate potential hazards. The study highlights the unique challenges faced by civil engineering laboratories, such as constantly changing physical environments and the presence of specific hazards related to experiments and tests. To address these challenges, the study proposes the integration of JSA into OSH frameworks, adapting methods like the Construction Job Safety Analysis (CJSA) to suit the dynamic nature of laboratory work. The research also emphasizes the importance of fostering a strong safety culture through employee awareness, training, and the use of innovative approaches like virtual reality (VR) in OSH education. By combining JSA techniques with comprehensive OSH initiatives, the study aims to improve hazard identification, risk assessment, and worker engagement in civil engineering laboratories. While the specific impact of integrating JSA into OSH practices on safety performance in civil engineering laboratories requires further research, the available literature suggests that such an approach can potentially enhance safety outcomes by establishing effective hazard control measures and promoting a proactive safety culture.